Bibliography. - Cardona, Mylynka Kilgore; Dupont, Colin (Imago Mundi, 2024)
This document is a bibliography that includes items published from 2019 to 2023. It covers a wide range of topics related to cartography and maps, including the visualization of urban maps, the history of cartography, the analysis of historical maps, and the exploration of different regions and cultures. The entries follow the International Standard Bibliographic Description for Monographic Publications and provide unique reference numbers for indexing purposes. Researchers interested in cartography and its applications will find valuable information in these sources.